The Role of Parents in Instilling the Habit of Prayer Worship in Children - Aslindah, Andi; Rahmi, Nikmat (Educationist: Journal of Educational and Cultural Studies, 2023)
This research is motivated by the importance of the nuances of children carrying out prayer services from an early age. Habituation that is continuously carried out can contribute to character building. In this case, it is parents who play a major role in helping children's development, including the issue of worship. The purpose of this study was to determine the role of parents in instilling the habit of praying in children from an early age. This study uses a qualitative method with a descriptive approach. Data collection was carried out by observation and interview methods with 5 research subjects of Muslim parents who had children aged 5-10 years. In this study, it was found that several ways were used by parents to sell in educating the habit of praying in children, namely through exemplary by giving examples, giving advice, giving attention and supervision and giving awards or punishments if they did not pray as a Muslim obligation. Give punishment aims to improve and pious children.